Rangelands Atlas Local Voices: The Dehesa silvopastoral system - Lüdeke, Ernestine (International Livestock Research Institute, 2021)
A description of the dehesa silvopastoral system by Ernestine Lüdeke, President, Fundación Monte Mediterráneo, Huelva, Spain. Filmed by Marco Buemi http://www.marcobuemi.com Produced by Fiona Flintan, Marco Buemi and Patrick Augenstein 2021